Clinical and economic burden of community-acquired pneumonia among adults in Europe. Issue 1 (20th August 2010) - Welte, T; Torres, A; Nathwani, D
Abstract : It is difficult to determine the impact of community-acquired pneumonia (CAP) in Europe, because precise data are scarce. Mortality attributable to CAP varies widely between European countries and with the site of patient management. This review analysed the clinical and economic burden, aetiology and resistance patterns of CAP in European adults. All primary articles reporting studies in Europe published from January 1990 to December 2007 addressing the clinical and economic burden of CAP in adults were included. A total of 2606 records were used to identify primary studies. CAP incidence varied by country, age and gender, and was higher in individuals aged ≥65 years and in men. Streptococcus pneumoniae was the most common agent isolated. Mortality varied from <1% to 48% and was associated with advanced age, co-morbid conditions and CAP severity. Antibiotic resistance was seen in all pathogens associated with CAP. There was an increase in antibiotic-resistant strains, but resistance was not related to mortality. CAP was associated with high rates of hospitalisation and length of hospital stay. The review showed that the clinical and economic burden of CAP in Europe is high. CAP has considerable long-term effects on quality of life, and long-term prognosis is worse in patients with pneumococcal pneumonia.